Juvenile dermatomyositis: clinical, laboratorial, histological, therapeutical and evolutive parameters of 35 patients - Adriana Maluf Elias Sallum; Maria Helena Bittencurt Kiss; Silvana Sachetti; Maria Bernadate Dutra Resende; Kelly Cristina Moutinho; Mary de Souza Carvalho; Clovis Arthur Almeida Silva; Suely Kazue Nagahashi Marie (Arquivos de Neuro-Psiquiatria)
This study was based on a prospective and a retrospective analysis of 35 patients who met Bohan and Peter criteria for juvenile dermatomyositis diagnosis.The mean follow-up time was three years ten months. Calcinosis was present in five (14.28 %) patients, cutaneous ulcers in four (11.42%), and systemic involvement in nine (27.71%) patients. All patients presented alterations in the serum levels of muscle enzymes, and all of them were submitted to muscle biopsy as a diagnostic procedure. Nine (25.71%) patients received corticotherapy prior to and 26 (74.28%) after the muscle biopsy. Chloroquine, methotrexate, cyclosporine, cyclophosphamide and intravenous immunoglobulin were used in patients with poor response to corticotherapy. Continuation of cutaneous manifestations was observed in 4 (11.43%) patients, laboratorial activity in 1 (2.85%), cutaneous and laboratorial activities in 3 (8.57%). Ten (28.57%) patients were out of activity, and 17 (48.57%) in remission at study end-point, on March 2002. Two (5.71%) patients died.